Challenging the status quo! Prilleltensky, I (1994) The morals and politics of psychology: Psychological discourse and the status quo. Albany, New York: State University of New York Press. 283 pages. - Bhana, Arvin (PINS-Psychology in Society, 2026)
Prilleltensky's book provides a penetrating and challenging critical analysis of psychology's role in maintaining the status quo. He presents an incisive account of psychology's current preoccupation with individuals, and its failure to render any significant commentary on the social implications of psychological theory and practice. "However innocent, this neglect results in a very consequential moral illiteracy ..." (p1).